Screening ionic liquids for developing advanced immobilization technology for CO2 separation - Dai, Zhengxing; Chen, Yifeng; Sun, Yunhao; Zuo, Zhida; Lu, Xiaohua; Ji, Xiaoyan (Frontiers in Chemistry, 2022)
Developing immobilized-ionic liquids (ILs) sorbents is important for CO2 separation, and prior theoretically screening ILs is desirable considering the huge number of ILs. In this study, the compressibility of ILs was proposed as a new and additional index for screening ILs, and the developed predictive theoretical model, i.e., electrolyte perturbed-chain statistical associating fluid theory, was used to predict the properties for a wide variety of ILs in a wide temperature and pressure range to provide systematic data. In screening, firstly, the isothermal compressibilities of 272 ILs were predicted at pressures ranging from 1 to 6,000 bar and temperatures ranging from 298.15 to 323.15 K, and then 30 ILs were initially screened. Subsequently, the CO2 absorption capacities in these 30 ILs at temperatures from 298.15 to 323.15 K and pressures up to 50 bar were predicted, and 7 ILs were identified. In addition, the CO2 desorption enthalpies in these 7 ILs were estimated for further consideration. The performance of one of the screened ILs was verified with the data determined experimentally, evidencing that the screen is reasonable, and the consideration of IL-compressibility is essential when screening ILs for the immobilized-IL sorbents.